Occupational therapists' experiences of career progression following promotion. (22nd June 2015) - Nelson, Helen; Giles, Susan; McInnes, Heather; Hitch, Danielle
Abstract : Background/Aim: The recruitment and retention of a skilled occupational therapy workforce is highlighted as a key issue for the profession, and yet there have been relatively few studies into the career progression of occupational therapists. Methods: A qualitative, naturalistic approach was adopted to answer the research question, using semi‐structured interviews to gather data. Eleven purposefully selected participants at an Australian health service were interviewed as part of this study. Categories representing the most common themes and topics supplied by participants within their individual interviews were identified and consolidated by the research team. The trustworthiness of this study was supported by strategies to maximise its credibility, dependability and confirmability. Results: Four main themes were elicited from the data – (i) Readiness for progression, (ii) Tools and processes, (iii) Expectations and (iv) What I wish I had known first. Within these themes, related findings were also identified by both Grade 2 and Grade 3 staff. Conclusions: This study indicates that the readiness of occupational therapists to climb the career ladder is influenced by the tools and processes they can utilise, and the expectations they have around the realities of their new position. With hindsight, participants highlighted some things they wish they had known at the time of transition, which appeared to have been implicit. Significance of Study: This study is the first to address the common issues for occupational therapy staff around progression between grade levels. It therefore provides a basis for further research in other practice settings and for the development of supports for therapists climbing the career ladder.